(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Gridhrasi is a Rujapradhana nanatmaja vata vyadhi, intervening with the functional ability of low back and lower limbs. Low back pain is the major cause of morbidity throughout the world affecting mainly the young adults. Life time incidence of low back pain is said to be 50-70% with the incidence of Sciatica more than 40%. Objective: The present study intended to focus on the disease evaluation i.e., Gridhrasi- Sciatica and combined effect of selective Yoga techniques and Sthanika Abhyanga in the management of Gridhrasi- Sciatica is undertaken. Study Design: Total study duration was 60 days, treatment duration was 30days. 30 patients full filling the inclusion criteria of Gridhrasi were randomly selected and divided in to 2 groups, Group A- Yoga Techniques. Group B- Yoga techniques and Sthanika Abhyanga. Containing 15 patients in each group and advised for Yoga techniques in morning Abhyanga with Tilataila in morning. Results: Group A, Group B shown significant effect after the treatment. Comparatively Group B (Yoga techniques & Sthanika Abhyanga) shown better result than Group A (Yoga Techniques).